Exploring Zoom fatigue among international students in the U.S. virtual classes - Son, Esther; Cvancara, Kristen (Journal of International Students, 2024)
Online video conferencing platforms, such as Zoom, are widely used for virtual classes. Zoom platforms bring flexibility and convenience but also contribute to fatigue, which is called “Zoom fatigue.” The purpose of this study is to investigate Zoom fatigue among international students at U.S. universities and its links to virtual classroom communication in the field of education. The study investigated how English competency and course engagement affected Zoom fatigue in virtual classes experienced by 152 international students. The results showed that English competency and course engagement had a negative relationship with Zoom fatigue. The study implied that when international students had high English competency, they had less Zoom fatigue experience. In addition, international students had less Zoom fatigue experience when they engaged in virtual classes. The study suggested future directions for decreasing Zoom fatigue and increasing course engagement among international students in virtual classes.